Seismic early warning systems for the transport cascade under the "SHIPKA" pass - Philip Philipoff; Violeta Komitova; Atanas Mangarov; Stanimir Karapetkov; Elka Radeva; Boyko Ranguelov; Simeon Panev; Blagovest Panev; Ina Antonova; Diana Bankova; Dimo Dimov (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
The report presents an early warning system against earthquakes of the conceptual design of the tunnels under the "Shipka" Pass. Bulgaria gives many victims on the roads - those killed in traffic crashes and accidents. In the case of tunnel facilities in seismic areas, chain accidents in tunnel pipes are particularly dangerous. Early warning systems for tunnels make it possible to immediately stop traffic by the traffic police or automatically, to include additional ventilation equipment and turn on the additional reserve lighting installations.